1995
DOI: 10.1152/ajpheart.1995.268.3.h1335
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ito in young and adult human atrial myocytes: evidence for developmental changes

Abstract: In an effort to understand the ionic basis for the developmental changes that have been reported to occur in the configuration of the human atrial action potential, we characterized the transient outward current (Ito) and the inward rectifier current in atrial myocytes isolated from 20 young (ages 1 day-2.5 yr) and 8 adult (11-68 yr) human hearts using the whole cell patch-clamp technique. We found evidence for statistically significant (P < 0.05) age-related changes in the Ito, including 1) the presence of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 0 publications
10
40
1
Order By: Relevance
“…(i) Isolation of cardiac myocytes. Human myocytes were obtained from specimens of human right atrial appendage obtained during surgery from hearts of patients undergoing cardiopulmonary bypass (12). Samples were quickly immersed in a cardioplegic solution consisting of 50 mM KH 2 PO 4 , 8 mM MgSO 4 , 10 mM NaHCO 3 , 5 mM adenosine, 25 mM taurine, 140 mM glucose, and 100 mM mannitol, titrated to a pH of 7.4, and bubbled with 100% O 2 at 0 to 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…(i) Isolation of cardiac myocytes. Human myocytes were obtained from specimens of human right atrial appendage obtained during surgery from hearts of patients undergoing cardiopulmonary bypass (12). Samples were quickly immersed in a cardioplegic solution consisting of 50 mM KH 2 PO 4 , 8 mM MgSO 4 , 10 mM NaHCO 3 , 5 mM adenosine, 25 mM taurine, 140 mM glucose, and 100 mM mannitol, titrated to a pH of 7.4, and bubbled with 100% O 2 at 0 to 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…19 Previous work by Wu et al 7 in rabbit myocytes has shown that age-related changes in the sensitivity of I K1 to quinidine may also occur. Although no developmental change in the characteristics of I K1 has been reported for human cardiac tissue, 12 it was difficult to rule out the possibility that postnatal changes in I K1 sensitivity to quinidine sensitivity may not also exist in human tissue. To define the effects of Comparison of the kinetics and voltage dependence of I to recovery from quinidine block in pediatric and adult myocytes.…”
Section: Effects Of Quinidine On I K1 I Sus and I Nsmentioning
confidence: 99%
“…Human atrial myocytes were isolated enzymatically from the obtained specimens. The isolation procedure was identical to that previously described by Crumb et al 12 and typically produced an initial yield of 40% to 60% rod-shaped, calcium-tolerant cells. Cells were used within 8 hours after isolation.…”
Section: Human Atrial Specimens and Isolation Of Cardiac Myocytesmentioning
confidence: 99%
See 2 more Smart Citations